Teungku Chiek Dirundeng's Struggle in Confronting Dutch Colonial - Syamsuar, Syamsuar (SCAD Independent, 2020)
This research discussed about the study of TeungkuChiekDirundeng’s struggle in confronting Dutch colonial. Teungku Chiek Dirundeng was one of the Moslem scholars and one of the fighters in South West Coast, who had developed human civilization and education through dayah. Moreover, he found the Dutch in order to defend the territory; the war was called by the Sabil (holy) war. The term of the Sabil War had motivated his troops and followers to have a high fighting spirit. This story was enshrined in Aceh story, namely Hikayat Teungku in Meukek. This research applied qualitative methods. It told about his birth and his struggle comprehensively. The data were collected through interviews, observation and Focus Group Discussion (FGD). The findings of this study revealed that Teungku Chiek Dirundeng as a respected figure in society. He was also identical with the dayah education since he had promoted establishing the dayah. Dayah was a building center for guiding the human to understand religious values and the sabil war ideology to defy Dutch colonial. There were some dayahs built by Teungku Chiek Dirundeng such as dayah in DamaTutong, in Meukek, in Plumat, in Labuhan Haji, and the last in Rundeng, Meulaboh. On the other hand, Teungku Chiek Dirundeng was a fighter who continually fought the Dutch. In 1893, he, along with his troops, had confronted with the other Muslims, namely Teuku Raja Hitam (UleeBalang/King of Meulaboh). In this war, Teungku Chiek Dirundeng and his troops got defeated because Ulee Balang was assisted by the Dutch.